Insight private equity - Andrej Gill; Nikolai Visnjic (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
We are able to shed light on the black box of restructuring tools private equity investors use to improve the operational performance of their portfolio companies. By building on previous work considering performance evaluation of PE backed companies, we analyze whether private equity improves operating efficiency and which of the typical restructuring tools are the main performance drivers. Using a set of over 300 international leveraged buyout transactions of the last thirty years, we find that while there is vast improvement in operational efficiency, these gains vary considerably. Our top performing transactions are subject to strong equity incentives, frequent asset restructuring and tight control by the investor. Furthermore, investors' experience has a positive influence while financial leverage has no influence on operational performance.
urn:nbn:de:hebis:30:3-305769
Keywords: G23; G24; G32; G34; 330; private equity; leveraged buyouts; active shareholders; corporate restructuring; operational performance